Experimental study on influence determination of temperature region of hot air to the refined sugar drying on the model of pulsed continuous fluidized bed dryer - Le , Hong Long; Pham , Quang Phu; Bui , Trung Thanh (Journal of Technical Education Science, 2020)
A pulsed fluidized bed dryer is used to experimental refined sugar (RS) drying. The experiments were conducted on the single factor experiments to determine the influence of the hot air temperature region (tg,°C) to the moisture content of the product (%), the collectable finished product efficiency (%), the specific electrical consumtion (Wh/kg finished product) and the specific heat consumption (kJ/kg finished product). The experimental model has its capacity of 20kg per hour with the 04 (four) fixed technological parameters during doing experiments such as the height of basic dried layer (H0, mm) is 65mm, the hot air velocity (vg, m/s) is 2m/s, pulsed frequency (f, Hz) is 0,5Hz and the mean diameter of RS (dp, mm) and the temperature region of hot air were adjusted from 70 to 80°C . The practical results are obtained that the quality of the dried grains met the TCVN 6958: 2001 with moisture content of finished product is 0,05- 0,06%, specific heat consumption is 1008÷1116 kJ /kg finished product), the specific electrical consumption is 193÷211 Wh/ kg finished product and the collectable efficiency of finished product is 87÷88%.